Challenges faced by occupational therapists and teachers in the implementation of vocational programmes in selected special needs schools for learners with severe intellectual disability in the metro district within the City of Cape Town - Solomon, Elana Tina (Stellenbosch : Stellenbosch University, 2023)
Thesis (MHumanRehabSt)--Stellenbosch University, 2023.